Soil Moisture Retention Characteristics and Hydraulic Conductivity for Different Areas in India in Selected States - C. P. Kumar; Sanjay Mittal (Journal of Soil and Water Conservation, 2022)
Mathematical models of hydrologic and agricultural systems require knowledge of the relationships between soil moisture content (q), soil water pressure (h) and unsaturated hydraulic conductivity (K). This study involved field and laboratory determination of soil moisture characteristics in different areas of India - Hindon, Kolar, Narsinghpur, Ghataprabha and Lokapavani. Saturated hydraulic conductivity was measured either through Guelph Permeameter in the field or through ICW Permeameter or Jodhpur Permeameter in the laboratory. Retention curve data was obtained through pressure plate apparatus. These have been used to develop empirical relationships to derive the approximate soil moisture retention curveat the places where only saturated hydraulic conductivity data is available.